2014
DOI: 10.1002/asi.23263
|View full text |Cite
|
Sign up to set email alerts
|

“They are always there for me”: The convergence of social support and information in an online breast cancer community

Abstract: This research examines interactions among members of an online breast cancer community, focusing on how information and social support were exchanged, how these exchanges influenced health decisions, and how the community was integrated into participants' everyday lives. This article is the result of a 2‐year ethnography comprising online archives analysis, participant observation, and 31 interviews. In the course of the research, the findings revealed that, not only did participants exchange valuable informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 68 publications
3
78
0
Order By: Relevance
“…This study confirmed the importance of SNS use for developing social support. This finding aligns with previous studies that suggested a positive relationship between participation in Internet‐based support groups and obtaining social support (Kroenke et al, ; Rubenstein, ) and ultimately improved psychological well‐being of cancer patients (Høybye et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study confirmed the importance of SNS use for developing social support. This finding aligns with previous studies that suggested a positive relationship between participation in Internet‐based support groups and obtaining social support (Kroenke et al, ; Rubenstein, ) and ultimately improved psychological well‐being of cancer patients (Høybye et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown social support to be a product of social connections (Chuang & Yang, ; Lin, Hsu, Cheng, & Chiu, ; Zhang & Yang, ) and a predictor of health outcomes, such as greater well‐being (Bui, Yen, & Honavar, ; Wright, ). Rubenstein () showed information and emotional support was exchanged among members of an online breast cancer group. In a study of the influence of social support on quality of life measures (including emotional and social well‐being) in 3,139 women who were diagnosed with and survived breast cancer from 2006 to 2011, greater social support was found to be related to higher emotional and social well‐being after diagnosis (Kroenke et al, ).…”
Section: Model and Hypothesesmentioning
confidence: 99%
“…The community gives them a feeling that they are part of a group of people who face similar challenges and endure experiences that are distinct from their healthy family members and friends, who are not always able to understand them. Social connections, a sense of belonging, and the need for empathy have been shown in prior studies to be significant reasons for continuing participation in an online community (Erfani et al, ; Lin & Huang, ) and that social support in its various formats functions as information that positively impacted members' actions and helped them make sense of their illness (Rubenstein, , ).…”
Section: Discussionmentioning
confidence: 99%
“…These online spaces shape social relationships via the Internet by means of a series of social interactions that exist only online among people who share a common interest or problem. Two key factors for participating in such communities are seeking or offering experiential information and social support (Erfani, Abedin, & Blount, 2016;Giles & Newbold, 2013;Reinke & Solheim, 2015, Rubenstein, 2015Vayreda & Antaki, 2009;Walther & Boyd, 2002;Zhang, 2016). Hence, the community's significance as a source for varied information and the nature of the social interaction between the members of the community that foster a sense of community shape the notion of these virtual spaces as "weak ties" (Adelman, Parks, & Albrecht, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…However, much of the previous research on health information behavior is descriptive in nature, focusing on sources selected, frequency of use, searching for themselves or others, and the impact of the Internet on health (Lorence et al., ; Powell et al., ) rather than the evaluation processes associated with selection. In addition, many of the studies that link gender and health information behavior are qualitative studies based on women‐only groups of participants (Genuis, ; Rubenstein, ; Sillence, Briggs, Harris, & Fishwick, ). Accordingly, there is scope for a more analytical approach to understanding online health information evaluation, and for research comparing the health information behavior of men and women.…”
Section: Introductionmentioning
confidence: 99%